AMMYSO: Antibacterial Gummy Soap Utilization of Used Cooking Oil with Syzygium Oleana Leaf Extract - Nur'ani, Rahma; Haniyah Salma Nur; Farras Inas Mumtaza; Najwa Amar Hanindya; Salsabila Nurdiyanto; Yesi Yuliani (SMA Trensains Muhammadiyah Sragen, 2024)
Used cooking oil is waste that comes from cooking oil used for culinary needs. Used cooking oil can be reprocessed into a variety of products, one of which is soap. Soap is a cleansing surfactant made by a chemical reaction between potassium or sodium and fatty acids from oils or fats. Red shoot leaves contain phenols, compounds, flavonoids, betulinic acid, alkaloids, triterpenoids, steroids, and saponins that can be utilized as antibacterials. AMMYSO (Antibacterial Gummy Soap) is an innovative antibacterial soap in the form of gummy soap. This study aims to utilize used cooking waste as the basic ingredient for making gummy soap with the addition of red shoot extract as an antibacterial. This research is descriptive with a qualitative approach. The tests carried out are organoleptic tests, homogeneity tests, pH tests, and antibacterial tests. The results of the organoleptic test showed that AMMYSO has a chewy texture, green color, and a distinctive aroma of red shoot leaves. The homogeneity test did not find any separate coarse particles. The pH test of the soap meets the appropriate pH standards. Antibacterial tests showed that AMMYSO was effective in inhibiting the growth of Staphylococcus aureus bacteria.